Microbial colonization patterns and biodegradation of petrochemical and biodegradable plastics in lake waters: insights from a field experiment - Di Pippo, Francesca; Bocci, Valerio; Amalfitano, Stefano; Crognale, Simona; Levantesi, Caterina; Pietrelli, Loris; Di Lisio, Valerio; Martinelli, Andrea; Rossetti, Simona (Frontiers in Microbiology, 2023)
Once dispersed in water, plastic materials become promptly colonized by biofilm-forming microorganisms, commonly known as plastisphere. By combining DNA sequencing and Confocal Laser Scanning Microscopy (CLSM), we investigated the plastisphere colonization patterns following exposure to natural lake waters (up to 77 days) of either petrochemical or biodegradable plastic materials (low density polyethylene -LDPE, polyethylene terephthalate -PET, polylactic acid -PLA, and the starch-based MaterBi® -Mb) in comparison to planktonic community composition. Chemical composition, water wettability, and morphology of plastic surfaces were evaluated, through Transform Infrared Spectroscopy (ATR-FTIR), Scanning Electron Microscopy (SEM), and static contact angle analysis, to assess the possible effects of microbial colonization and biodegradation activity. The phylogenetic composition of plastisphere and planktonic communities was notably different. Pioneering microbial colonisers, likely selected from lake waters, were found associated with all plastic materials, along with a core of more than 30 abundant bacterial families associated with all polymers. The different plastic materials, either derived from petrochemical hydrocarbons (i.e., LDPE and PET) or biodegradable (PLA and Mb), were used by opportunistic aquatic microorganisms as adhesion surfaces rather than carbon sources. The Mb-associated microorganisms (i.e. mostly members of the family Burkholderiaceae) were likely able to degrade the starch residues on the polymer surfaces, althoughthe Mb matrix maintained its original chemical structure and morphology. Overall, our findings provide insights into the complex interactions between aquatic microorganisms and plastic materials found in lake waters, highlighting the importance of understanding the plastisphere dynamics to better manage the fate of plastic debris in the environment.